2012
DOI: 10.1136/jclinpath-2011-200630
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic impact of desmocollins in human lung cancer

Abstract: Objective Desmosomes are intercellular junctions that confer strong cell-cell adhesion. Two main members of desmosomal cadherins, desmogleins (DSGs) and desmocollins (DSCs), are involved in carcinogenesis. However, their role in human lung cancer remained elusive. The aims of this study were to analyse the expression of DSCs and to evaluate their clinical application in lung cancer. Methods The expression of DSC1-3 mRNAs was analysed by RT-PCR. The methylation status of DSCs was analysed by demethylation tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
(27 reference statements)
1
27
1
Order By: Relevance
“…Sensitivity of DSC3 for squamous NSCLC is 93.2% in large cohort of 426 but drops to 59% in poorly differentiated squamous NSCLC (Table 1). DSC3 expression in NSCLC is also not related to stage or histologic grade [17] of a disease [46].…”
Section: Lmentioning
confidence: 98%
See 1 more Smart Citation
“…Sensitivity of DSC3 for squamous NSCLC is 93.2% in large cohort of 426 but drops to 59% in poorly differentiated squamous NSCLC (Table 1). DSC3 expression in NSCLC is also not related to stage or histologic grade [17] of a disease [46].…”
Section: Lmentioning
confidence: 98%
“…Immunohistochemistry reveals in lung cancer expression of DSC3 is seen at basal layers of tumor. DSC3 expression is seen in around 30% of cases [17]. DSC 3 expression is seen in squamous NSCLC and not in adenocarcinoma of lung.…”
Section: Desmocollin-3 and Cancermentioning
confidence: 98%
“…Slug has also been implicated in FGF-1-induced alterations in border localization of Dsg1/2 and desmoplakin in NBT-II bladder carcinoma cells (Savagner, et al, 1997, Thiery and Chopin, 1999). DNA methylation also plays a role in the reduced expression of Dsc1, Dsc2, Dsc3 and desmoplakin in lung cancer (Cui, et al, 2012a, Cui, et al, 2012b). Furthermore, the protease kallikrein has been linked to the reduced expression of Dsg1 and Dsg2 in pancreatic adenocarcinoma (Ramani, et al, 2008).…”
Section: Acquired Desmosomal Diseasesmentioning
confidence: 99%
“…They noticed that DSC1-3 mRNAs were down regulated in lung cancer cells. In a study that included 199 patients with a history of primary lung cancer, they found that DSC3 proteins were more expressed in SCC compared with ADC (p < 0.001), and that reduced expression of DSC3 was correlated with poor clinical outcome [32].…”
Section: Discussionmentioning
confidence: 99%